2007
DOI: 10.1111/j.1600-6143.2007.01839.x
|View full text |Cite
|
Sign up to set email alerts
|

Different Mechanisms Control Peripheral and Central Tolerance in Hematopoietic Chimeric Mice

Abstract: Regulatory T cells (Treg) are important in peripheral tolerance, but their role in establishing and maintaining hematopoietic mixed chimerism and generating central tolerance is unclear. We now show that costimulation blockade using a donor-specific transfusion and anti-CD154 antibody applied to mice given bone marrow and simultaneously transplanted with skin allografts leads to hematopoietic chimerism and permanent skin allograft survival. Chimeric mice bearing intact skin allografts fail to generate effector… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 46 publications
(98 reference statements)
3
24
0
Order By: Relevance
“…Whether the increased percentage of Foxp3-positive donor CD4 ϩ cells is derived from preexisting nTreg or due to de novo induction of adaptive Treg is at present unknown. Several studies have already suggested that the result of costimulation blockade is at least partially based on the induction of Treg (33)(34)(35). We previously demonstrated that human T cell activation by costimulatory signaldeficient allogeneic cells induces anergic T cells with regulatory activity (36).…”
Section: Discussionmentioning
confidence: 99%
“…Whether the increased percentage of Foxp3-positive donor CD4 ϩ cells is derived from preexisting nTreg or due to de novo induction of adaptive Treg is at present unknown. Several studies have already suggested that the result of costimulation blockade is at least partially based on the induction of Treg (33)(34)(35). We previously demonstrated that human T cell activation by costimulatory signaldeficient allogeneic cells induces anergic T cells with regulatory activity (36).…”
Section: Discussionmentioning
confidence: 99%
“…In those studies, the impact of Treg-depletion might be insufficient to induce allogeneic hematopoietic cell rejection because they used stronger immune suppression or lower immunological barrier models than ours. Other supportive studies described the abrogation of mixed chimerism induction with anti-CD25 mAb in the lower invasive protocol setting of fully-allo combination (27,51). It is presumable that there is a delicate balance between Tregs and effector T cells (Teffs) in allograft tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Skin grafts Autoimmunity (Oderup et al, 2006) Il2Rbeta-/-recipients Heart (Oderup et al, 2006) Rag 1 -/-given anti-154 and anti-B7 Chimerism (Iudaev et al, 1975) Sublethal WBI and BMC Hy antigen and HVG (Weng et al, 2007) Sublethal WBI Chimerism Skin allografts (Yamazaki et al, 2007) BMC, DST and anti-CD154…”
Section: Graft or Target Authors Methods Of Inductionmentioning
confidence: 99%